Controlling African cassava mosaic disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Controlling African cassava mosaic disease CTA has published a 20-page booklet, written by John Guthrie